Penerapan Sistem Manajemen Hygiene Industri dalam Upaya Peningkatan Kesehatan Pekerja di Lingkungan Kerja - Alfira Budiman; Dinda Rizky Fadillah; Nazwa Nazwa; Abdurrozzaq Hasibuan (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2026)
Industrial hygiene management plays a critical role in protecting worker health by controlling exposure to hazardous factors in the workplace. However, many work environments still show suboptimal implementation, leading to increased risks of occupational diseases. This study aims to analyze the implementation of industrial hygiene management systems in improving worker health based on a literature review approach. The method used is a literature review by collecting and analyzing scientific articles from national databases published between 2021 and 2026. A total of ten relevant articles were selected through a systematic screening process based on predefined inclusion criteria. The findings indicate that workplace hazards such as physical, chemical, and ergonomic factors are significantly associated with various health problems, including respiratory disorders, musculoskeletal issues, and work-related fatigue. The implementation of industrial hygiene management systems, including hazard identification, risk control measures, use of personal protective equipment, and environmental monitoring, has been shown to reduce health risks among workers. However, the effectiveness of implementation is influenced by factors such as worker compliance, management commitment, and availability of facilities. These results highlight the importance of a comprehensive and systematic approach to industrial hygiene in maintaining worker health and preventing occupational diseases. Therefore, strengthening the implementation of industrial hygiene management systems is essential to create a safe and healthy working environment and to support sustainable occupational health practices.